Antifouling paints with zinc "tannate" - Bellotti, Natalia (2010)
During the past decade, the necessity of new ecofriendly antifouling pigments was established. Among these new pigments, special attention should be paid to tannin and its derivatives. Tannins are synthesized by plants as part of their defense mechanism against the attack of pathogens. The objective of this work was to study the antifouling efficiency of paints containing zinc "tannate" in artificial seawater. The zinc "tannate" was precipitated at pH 4 and pH 8. Insoluble and soluble matrix antifouling paints, with different plasticizers, were formulated and tannins leached from the paints immersed in artificial seawater were determined by the Folin-Denis assay for polyphenols. The antifouling action of paints was assessed in a natural seawater environment. The results showed that the leaching rate of tannin from insoluble matrix paint decreases, reaching a constant value after 25 days of immersion. In the case of the soluble matrix paints, a lesser amount of tannin was leached, depending on the tannin and the plasticizer employed. The results in a natural sea environment are dependent on the matrix and the plasticizer employed.